Pengaruh Pengetahuan Akuntansi terhadap Penerapan Akuntansi Digital serta Dampaknya terhadap Kinerja UMKM - Aryanto, Aryanto; Amaliyah, Fitri (Universitas Pamulang, 2022)
MSME actors have not been able to fully utilize the use of technology, this is a challenge for MSME actors in Indonesia. This study aims to determine the effect of accounting knowledge of MSME actors on the application of digital accounting and its impact on MSME performance. The type of data in this study is quantitative data with the primary data source from a questionnaire. The population in this study is MSMEs in the Brebes District, Brebes Regency with a sample of 65 MSMEs using a simple random sampling technique. The data analysis technique in this study used the SEM Partial Least Square (PLS) method. The result showed that the level of accounting knowledge has a significant positive effect on the application of digital accounting, the level of accounting knowledge has no effect on performance, and the application of digital accounting has a significant positive effect on performance.